Dental consultations requested to the maxillofacial surgery division in a hospital in Brazil - Longoni, Camila; Corsetti, Adriana; Freddo, Angelo Luiz; Puricelli, Edela; Ponzoni, Deise (Clinical and Biomedical Research, 2020)
Introduction: This study analyzed dental consultation requests to the division of oral and maxillofacial surgery in a Brazilian tertiary hospital. Methods: A cross-sectional study with data collected retrospectively from inpatients’ electronic medical records containing dental consultation requests made between January 2013 and December 2017. Results: 327 consultation requests were analyzed. Mean (SD) patient age was 38.71 (24.4) years; 164 (50.2%) were male and 267 (81.7%) were Caucasian. Regarding systemic conditions, 34 (10.4%) were classified as ASA I, 86 (26.3%) as ASA II, 182 (55.7%) as ASA III, and 25 (7.6%) as ASA IV. Dental consultations were mostly requested by the internal medicine team (n = 42, 12.8%). The most common reason for consultation was septic teeth (n = 131, 40.1%). Complementary tests were required in 188 (57.5%) cases. Surgical intervention was required in 82 (25.0%), with tooth extraction as the most prevalent procedure (20.2%). The most demanding service was inpatient care, with 276 (84.4%) requests. Cases were resolved in 249 (76.1%). Conclusions: The division of oral and maxillofacial surgery in our hospital deals with a great amount of consultations, contributing with surgical procedures to the adequacy of patients’ oral health with a high effectiveness rate. Our data illustrate the contribution of dentists in a hospital setting, assisting the medical team in providing comprehensive care for inpatients. Keywords: Dental consultations; inpatients; oral and maxillofacial surgery